2015
DOI: 10.17507/tpls.0505.15
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Accuracy of Self- and Peer-assessment of Iranian Intermediate EFL Learners and Their Learning Styles

Abstract: Abstract-Within the last few decades, with the growing emphasis on learner-centered curriculum, selfassessment and peer-assessment have become of particular interest in educational assessment. This study aimed at examining the relationship between the accuracy of self-and peer-assessment on the paragraph writing performance of a sample of Iranian intermediate EFL students and their learning styles. To do so, 7 paragraphs during 7 sessions were written and then self-and peer-rated by 62 students from Touba Lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This finding is consistent with our assumption that conducting appropriate training prior to undertaking SA can improve correlations with external measures. Through a careful survey of the primary studies (e.g., Birjandi & Bolghari, 2015), we found that the training was mainly delivered through workshops or tutorials under the guidance of experienced instructors/researchers with demonstrated examples and explanations of the necessary terminology. Furthermore, during the training process, learners were guided to practice SA multiple times and their behaviors were checked and corrected by the instructors/researchers in order to ensure that learners with varying SA experience and assessment abilities could reach an equal understanding of both the manner of SA (i.e., the SA forms) and the assessment criteria (i.e., the SA content) (Brown & Harris, 2013; Orsmond et al., 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with our assumption that conducting appropriate training prior to undertaking SA can improve correlations with external measures. Through a careful survey of the primary studies (e.g., Birjandi & Bolghari, 2015), we found that the training was mainly delivered through workshops or tutorials under the guidance of experienced instructors/researchers with demonstrated examples and explanations of the necessary terminology. Furthermore, during the training process, learners were guided to practice SA multiple times and their behaviors were checked and corrected by the instructors/researchers in order to ensure that learners with varying SA experience and assessment abilities could reach an equal understanding of both the manner of SA (i.e., the SA forms) and the assessment criteria (i.e., the SA content) (Brown & Harris, 2013; Orsmond et al., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of their relationship with SA, language tests have shown moderate to high correlations with SA (e.g., .75 -.96 in Bachman &Palmer, 1989 and.66 in Ikeguchi, 1996). For teacher assessment, the results are more mixed as some studies recorded high correlations (e.g., .61 -.84 in Birjandi & Bolghari, 2015) and others reported weak or non-significant correlations (e.g., .05 in Langan et al, 2008). Therefore, it is hypothesized that the type of external measure is likely to affect the correlation magnitude.…”
Section: External Measuresmentioning
confidence: 99%
“…The third factor that is considered to play a role in the miscalibrations is IDs. Research on L2 self-evaluation has investigated several ID factors, such as gender (Pallier 2003), proficiency (e.g., Brantmeier et al 2012;Strong-Krause 2000), L2 learning experience (e.g., Suzuki 2015 for L2 reading skill), and self-evaluation training/experience (e.g., Birjandi and Bolghari 2015). Using Can-Do statements, Suzuki (2015) examined 63 Japanese learners' self-evaluations of Chinese reading skills.…”
Section: Individual Differences and L2 Speechmentioning
confidence: 99%
“…Self-assessment is connected to the students' involvement in evaluating their learning, particularly their accomplishments and the outcomes of their learning (Birjandi & Bolghari, 2015). Peer evaluation and cooperative learning go hand in hand (Fulcher & Davidson, 2007).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The practice of accepting responsibility for learning and assessment enables the student to develop greater autonomy and self-governance (Chen, 2008). Self-assessment is connected to the students' involvement in evaluating their learning, particularly their accomplishments and the outcomes of their education (Birjandi & Bolghari, 2015). The use of self-assessment in the classroom helps students play a more active part in their education.…”
Section: Review Of the Literaturementioning
confidence: 99%